2009
DOI: 10.1371/journal.pone.0007021
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of TRPV1 Expressing Sensory Nerve Terminals in the Spinal Cord for Long Lasting Analgesia

Abstract: Chronic pain is a major clinical problem and opiates are often the only treatment, but they cause significant problems ranging from sedation to deadly respiratory depression. Resiniferatoxin (RTX), a potent agonist of Transient Receptor Potential Vanilloid 1 (TRPV1), causes a slow, sustained and irreversible activation of TRPV1 and increases the frequency of spontaneous excitatory postsynaptic currents, but causes significant depression of evoked EPSCs due to nerve terminal depolarization block. Intrathecal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 56 publications
15
136
0
Order By: Relevance
“…Our findings that activation of TRPA1 produced an initial 'depolarization block' and an extensive and sustained inhibition of voltage-gated calcium and sodium currents in DRG neurons provide a mechanism for the antinociceptive effect of spinal TRPA1 activation. This is in line with previous studies, showing that activation of TRPV1 produces a sustained inhibition of voltage-gated calcium and sodium channels [35][36][37][38][39] in sensory neurons as well as spinal antinociception 30,31,48 . On the basis of these studies, a model for TRPA1-mediated inhibition of synaptic transmission emerges, in which sodium and calcium influx through TRPA1 produces an initial depolarization-induced inactivation of voltage-gated sodium channels and a sustained inhibition of voltage-gated sodium and calcium currents, reducing action potential-dependent neurotransmitter release (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings that activation of TRPA1 produced an initial 'depolarization block' and an extensive and sustained inhibition of voltage-gated calcium and sodium currents in DRG neurons provide a mechanism for the antinociceptive effect of spinal TRPA1 activation. This is in line with previous studies, showing that activation of TRPV1 produces a sustained inhibition of voltage-gated calcium and sodium channels [35][36][37][38][39] in sensory neurons as well as spinal antinociception 30,31,48 . On the basis of these studies, a model for TRPA1-mediated inhibition of synaptic transmission emerges, in which sodium and calcium influx through TRPA1 produces an initial depolarization-induced inactivation of voltage-gated sodium channels and a sustained inhibition of voltage-gated sodium and calcium currents, reducing action potential-dependent neurotransmitter release (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The net result of these actions is inhibition of C-fibre-evoked postsynaptic excitation, although TRPA1-mediated calcium influx may initially increase spontaneous excitatory postsynaptic currents via activation of ionotropic glutamate receptors (iGluR) 42,[49][50][51] . similar molecular mechanisms have been advanced to explain the antinociceptive effect of spinal TRPV1 activation 31,48 . its electrophilic metabolites.…”
Section: Discussionmentioning
confidence: 90%
“…capsaicin is in line with previous studies which reported reduced neuropeptide content in the dorsal horn after desensitization of capsaicin-sensitive central afferent terminals with high dose TRPV1 agonists [22,32]. Remaining CGRP staining possibly corresponded to the peptidergic afferent population not expressing TRPV1 [50].…”
Section: Effects Of Trigeminal Ganglion Denervation On Cgrp-expressinsupporting
confidence: 92%
“…[9,25,32,50]. Thus, BoNT/A might prevent glutamate as well as other co-transmitters' release from a distinct set of nerve endings [19,21].…”
Section: Enzymatic Activity Of Bont/a In Tnc Occurs In Central Afferementioning
confidence: 99%
“…One hypothesis for this desensitization is that low level activation of TRPV1 with certain structures may be sufficient to evoke complete tachyphylaxis, without increasing the intracellular Ca 2+ concentrations to those levels needed to induce vasoconstriction. Alternatively, tachyphylaxis may be the reason for the irreversible activation of TRPV1 by resiniferatoxin (Jeffry et al, 2009) leading to a sustained Ca influx. To measure the level of activation needed to evoke tachyphylaxis a partial agonist (JYL-1511) was used.…”
Section: Pharmacology Of Trpv1 In Peripheral Arteriesmentioning
confidence: 99%